Ultra-high bit rate optical soliton communication - Shum, Ping (2008)
We start the project by first investigating the building blocks of active mode-locked erbium doped fiber ring soliton laser, which includes the laser cavity design, gain medium and pump source, filter and modulator designs. For better stability, regenerative structure has also been constructed, where the driving signal is direcdy derived from the output signal. Furthermore, the laser system behaviors have also been studied, such as the system noise, temporal and spectra analyses, and other observations.